Phytochemical study of the roots of malunggay, Moringa oleifera - Balmes, Ruben P.
There were several tests that were employed in the preliminary tests. It came out that glycosides, mucins, reducing substances, saponins and volatile oil are present. With the Lieberman-Burchard reagent, it confirmed the presence of saponins which is possibility heterosides of saturated sterols or saturated triterpenes. Two proximate analyses were performed. Its moisture content is 6.2 percent and its total ash is 11% and its acid-insoluble ash is 5.55%. The glycoside and the volatile oil were unsuccessfully extracted.